CFD simulation of flows around a swimmer in a prone glide position - Sato, Y.; Hino, T. (Japanese Journal of Sciences in Swimming and Water Exercise, 2010)
Flows around a swimmer's body in a prone glide position are computed with a Computational Fluid Dynamics (CFD) technique in order to understand the effect of a body shape on flow characteristics. A human model which consists of artificial bones, joints and an overlying skin is used to model the body shape in the consistent form via manipulation of the joints. A finite-volume based Navier-Stokes solver is used with unstructured tetra, prism and hexahedral grids for the flow computation to cope with the complicated geometry of a human body. The computed results of the underwater swimming show that the pressure drag is more than six times larger than the frictional drag. Various types of longitudinal vortices, flow separations and reattachments are observed due to the concave and convex geometry of the body. The parameter study for the gliding depth is conducted to evaluate the free-surface effects and the wave making resistance. The deformation of free-surface is computed reasonably well and it is shown that the wave making resistance can be estimated by the CFD technique.